3 - Ethnicity as an Independent variable in African Politics. Lessons learned from the 2017 Kenya Presidential Elections: - Paul Tang Abomo (African Sociological Review, 2021)
The aim of this study2 is to examine African voter behavior and the implications of ethnicity in African politics learning lessons from the Kenyan presidential elections of 2017. Other factors structuring voting behavior are explored including income, education, religion and social status. The study was conducted from May 13th to May 18th 2017, i.e., three months before election day. The population surveyed consisted of registered voters in the 49 counties of Kenya. Registration was determined by self-report. The sample frame was a cell telephone sample using a random digit dialing design. The sample was designed to be representative of the country of Kenya. As expected, the results showed that ethnicity is a strong predictor of voter behavior. However, variables like education, income, and age have an impact in mitigating the power of ethnicity. The more people get educated and wealthy the less they vote along ethnic lines. The younger voters are the less they side with their ethnic folks.